Influence of Ce3+ on the Structural, Morphological, Magnetic, Photocatalytic and Antibacterial Properties of Spinel MnFe2O4 Nanocrystallites Prepared by the Combustion Route - Salma A. Al-Zahrani; A. Manikandan; K. Thanrasu; A. Dinesh; K. Kanmani Raja; M. A. Almessiere; Y. Slimani; A. Baykal; S. Bhuminathan; S. Raghavendra Jayesh; Jahir Ahmed; Hajar S. Alorfi; et al. (Crystals, 2022)
The present work describes the effect of Ce3+ ion doping on the structural, morphological, and magnetic properties of spinel manganese ferrite (MnFe2O4) nanocrystallites (NCs) using various instrument techniques. Rare earth element (REE) Cerium (Ce3+) doped MnFe2O4 NCs were prepared by a simple microwave combustion technique. In the present scenario, ferrites are widely used for photocatalytic dye degradation and antibacterial applications. Aiming to achieve this, we prepared Ce3+ doped MnFe2O4 NCs by microwave combustion method and urea as burning agent and the obtained powder samples were characterized by powder X-ray diffraction (XRD), Fourier transform infrared (FT-IR), high resolution scanning electron microscope (HR-SEM), high resolution transmission electron microscope (HR-TEM) and vibration sample magnetometer (VSM) techniques. The pure spinel phase formation was confirmed by XRD analysis. FTIR spectra show two prominent absorption bands under 1000 cm−1, which confirms the formation of the spinel structure. HR-SEM and HR-TEM pictures demonstrated a sphere-shaped morphology and also expose the combination and agglomeration of grains, which are mostly due to the magnetic characteristics of the samples. The magnetic properties of the synthesized MnCexFe2−xO4 (x = 0.0, 0.1, 0.3, and 0.5) NCs were studied by VSM analysis at room temperature (RT) shows ferromagnetic behavior. The photodegradation results showed that MnFe2O4 and Ce doped MnFe2O4 NCs have a higher potential to degrade methylene blue (MB) and the sample MnCe0.3Fe1.7O4 NCs showed superb photocatalytic performance (91.53%) compared to other samples. The antibacterial activities of Gram-positive S. aureus, B. subtilis and Gram-negative K. pneumonia and E. coli were investigated using pure and Ce3+ substituted MnFe2O4 NCs and a higher activity for MnCe0.3Fe1.7O4 NCs than other samples was observed, which indicated that they can be used in biomedical applications.